Three tools that improve and expand Dropbox. IN Create. - Bohon, Cory.
Expand your Dropbox usage by requesting files, printing directly from Dropbox, and even using it with iWork on your iPad.
Keywords: iPad (Computer); iOS (Electronic resource); iWork; Dropbox